Observation of a peaking structure in the J/ψφ mass spectrum from B± → J/ψφK± decays - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (ELSEVIER, 2014)
A peaking structure in the J/psi phi mass spectrum near threshold is observed in B-+/- -> J/psi phi K-+/- decays, produced in pp collisions at root s = 7 TeV collected with the CMS detector at the LHC. The data sample, selected on the basis of the dimuon decay mode of the J/psi, corresponds to an integrated luminosity of 5.2 fb(-1). Fitting the structure to an S-wave relativistic Breit-Wigner lineshape above a three-body phase-space nonresonant component gives a signal statistical significance exceeding five standard deviations. The fitted mass and width values are m = 4148.0 +/- 2.4 (stat.) +/- 6.3 (syst.) MeV and Gamma = 28(-11)(+15) (stat.) +/- 19 (syst.) MeV, respectively. Evidence for an additional peaking structure at higher J/psi phi mass is also reported. (C) 2014 The Authors. Published by Elsevier B.V.
Keywords: Astronomy & Astrophysics; Physics